The Digitized First Byurakan Survey Database. Late-type stars candidates. New confirmations - Gigoyan, K. S.
More than 3000 Late-Type Stars (LTS) candidates was confirmed among the sample, selected on the Digitized First Byurakan Survey (DFBS) spectral plates. The DFBS is the digitized version of the First Byurakan Survey (FBS, or Markarian survey). This objective-prism survey was carried out in 1965-1980 by B. E. Markarian and colleagues using the 1 m Schmidt telescope of the Byurakan Astrophysical Observatory (BAO). FBS spectral plates have been used long period to search and study faint LTS (Ctype (carbon) and M-type) stars at high Galactic latitudes. Thousands of objects was confirmed as LTS. The confirmation is based on Gaia DR3 BP/RP low-resolution spectral database. In previous studies of the DFBS plates, these objects were presented as LTS candidates. Some objects are located more than 10 kpc. The predominant part of the new confirmed objects are M dwarfs.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture